Ecotourism Consumption Values in the Unfamiliar Market and Mediating Role of Destination Image - Mobeen Jamshed Khattak; Dr. Jamshed Khan; Bashir Khan (Journal of Business & Tourism, 2021)
This empirical study aims to determine the dimensions of the perceived value that are considered by the market that is unfamiliar to the ecotourism in relation to ecotourism purchase intention. The study also examines the role of destination image as mediators on the relation between perceived value and ecotourism purchase intention. Data was collected through a survey by self-administered structured questionnaire. The data from 355 respondents are analyzed using descriptive statistics, confirmatory factor analyses and regression analysis. The study findings reveal that three significant predictors i.e. conditional value, emotional value and epistemic value influence ecotourism purchase intention in the unfamiliar market. The strongest influence comes from conditional value, followed by emotional value and epistemic value. Result of this study also reveals that perceived value consisting of these three dimensions significantly influences ecotourism purchase intention. Destination image partially mediate relationship between perceived value and ecotourism purchase intention. This study concludes that only three perceived values significantly affect ecotourism purchase intention in the unfamiliar market. The conceptual model of this study is grounded in the priori causal model. Inferring strong causal effect may be considered as a limitation as it is not based on mixed models method. For deep understanding of the metaphor of values, future studies can carry qualitative investigation by experimental designs or focus groups. Connivance sampling technique also put limitation on the generalization of the study. The present study add to comprehensive understanding about the perceived values that are evaluated by individuals who are unfamiliar with ecotourism. While there is extensive research both for demand and supply in the area of ecotourism, this studyprovide the perceived values considered by the potential tourists who are unfamiliar to ecotourism.